STATE OF HEALTH AND WAYS TO RECOVERY CHILD POPULATION (Modern American Journal of Medical and Health Sciences, 2025)
Public health is one of the most important values in modern society and a strategic resource for the state. Public health directly impacts socioeconomic development, productivity, and quality of life. Recent decades have seen an increase in chronic diseases, a decline in physical activity, and an increase in stress factors, making public health a particularly pressing issue. Public health promotion involves a range of measures aimed at disease prevention, strengthening physical, mental, and social health, fostering a healthy lifestyle, and creating favorable living conditions. Effective public health promotion requires a comprehensive approach, including physical activity, balanced nutrition, prevention of unhealthy habits, psycho-emotional support, and improvement of the environmental and social environment.